Emerging Opportunities for Ambient Intelligence in Creativity Support Tools - Gonçalves, Fredericaand Fermé, Eduardoand Ferreira, João C.; Ferreira, J. (Intelligent Systems Design and Applications: 16th International Conference on Intelligent Systems Design and Applications (ISDA 2016) held in Porto, Portugal, December 16-18, 2016, 2017)
The fundamental challenge in developing and evaluating creativity support tools is that we are not able to detect when a person is being creative. In this position paper we described our perspective of ambient intelligence in creativity support tools specially in the use of creative writing environments. Starting with the activity theory, we describe a simple analysis of writing sessions involving 100 students from a higher school, and recorded using a keystroke logging program called Inputlog and the program iTALC to support it. Specifically, we outline the writing activity goals and the interaction design goals.